The reality of administrative leadership in Sudanese banks from the employees' perspective - Alhamdan, Khalel Alhamo (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to explore the reality of administrative leadership in Sudanese banks from the employees' perspective, focusing on the impact of leadership. The researcher adopted a descriptive analytical approach that combines the description of phenomena and the analysis of social and administrative relationships. The study population consisted of all employees in Sudanese banks, and a random sample of 200 employees was selected, with 165 responding. The sample included demographic variables such as gender, age, educational qualification, and years of experience in the banking sector. The study was conducted in 2023. The study population consisted of all employees in Sudanese banks, and a random sample of 200 employees was selected, with 165 responding. The sample included demographic variables such as gender, age, educational qualification, and the number of years of experience in the banking sector. The study utilized a questionnaire to measure the dimensions of administrative leadership, and the data were analyzed using statistical and qualitative methods. The results showed that the overall approval rating for the administrative leadership questionnaire was high, with an average of 3.82, while employee satisfaction ranked the lowest at an average of 3.71.The results also included an analysis of statistically significant differences between the average scores of the sample members, where tests indicated no statistically significant differences based on gender, age, or educational qualification. However, there was a statistically significant difference in the average scores of the administrative leadership questionnaire based on years of experience, with results favoring those with more than 10 years of experience.The findings indicated that administrative leadership in Sudanese banks exhibited professional competence and effective communication, which enhanced trust among employees. However, there is a need to improve certain aspects of employee satisfaction, such as appreciation and professional development.
Keywords: Employees; Leadership; Performance; Questionnaire; Satisfaction; Training